DEVELOPMENT OF THE INTELLECTUAL POTENTIAL OF THE ENTERPRISE: INNOVATIVE CHANGES AND DIGITALIZATION - DOROSHENKO, Vitaliy (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The development of the intellectual potential of the enterprise is one of the key strategic directions in the conditions of the modern business environment. Intellectual potential includes the knowledge, skills, experience and creativity of employees, which play an important role in competition and ensure the company's success in the market. The purpose of the presented work is the formation of the structure of the development of the intellectual potential of the enterprise under the influence of innovative changes and digitalization. The main methods that were used in the work are: methods of analysis and synthesis to determine the main components of the intellectual potential of the enterprise, the method of deduction and induction to determine the main directions of the development of the intellectual potential of the enterprise, the comparative method, the logical method, the graphic method to visually present the research results. The main result of the presented work is the determination of aspects of the development of the intellectual potential of the enterprise, which includes: investing in the professional development of employees, conducting trainings, seminars and training courses to improve their knowledge and skills; development of a corporate culture that promotes creativity, innovation and open exchange of ideas among employees; implementation of the latest technologies and software solutions to optimize business processes, automate work and increase labor productivity; development of flexible strategies and management methods that allow the enterprise to quickly respond to changes in the internal and external environment; participation in joint projects, experience exchange programs and initiatives to increase intellectual exchange. Digital technologies play an increasingly important role in modern business. The implementation of digital solutions can become a key factor in increasing the efficiency of operations, automating business processes, increasing the accuracy and speed of management decision-making, improving the level of customer service and increasing profitability. One of the key success factors of an enterprise is its ability to attract, develop and retain talented employees. For this, it is important to create favorable conditions for self-realization of employees, provide them with opportunities for professional growth and training, and also stimulate a creative approach to solving tasks. The development of the intellectual potential of the enterprise allows to create competitive advantages, to ensure stability and success in the market, as well as to maintain leadership in conditions of rapid changes and instability.
Keywords: potential; innovative changes; transformation; intellectual potential; intellectualization; entrepreneurial activity; transformational changes; digital technologies; digitalization; digital economy